Pemikiran Ekonomi pada Masa Ibnu Khaldun - S.A. Safry Saing; Syafitri Jaida; Besty Aprilia; Salsabila Balqis; Rauf Margana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Ibn Khaldun is a Muslim thinker whose contribution to Islamic economics is monumental, especially through the work of Al-Muqaddimah which discusses the theory of work value, market mechanisms, taxation, the role of the state, and the cycle of civilization. This journal aims to analyze his economic thought in depth through a literature study of 30 scientific journals using a qualitative approach with thematic analysis. The research method used is a qualitative approach with thematic analysis techniques from various scientific literature that examines Ibn Khaldun's thought in classical and modern contexts. The results of the study show that Ibn Khaldun's economic concepts are not only normative and historical, but also have applicative value in answering contemporary economic problems, including social inequality, the tax system, to sustainable economic development. Therefore, Ibn Khaldun's thought has a high relevance to be applied in the development of modern Islamic economics. His intellectual legacy is a bridge between Islamic values and scientific solutions to the global economic crisis.